2014
DOI: 10.1016/j.compscitech.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of dielectric property change to composite material state degradation

Abstract: a b s t r a c tPolymer matrix composites are widely used in many industries, i.e. aerospace, microelectronics, energy storage etc., because of their unique properties and performance. During their service life, changes of material state caused by deformation and damage accumulation under combined mechanical, thermal and electrical fields requires fundamental understanding to support design of those material systems. Heterogeneous material systems are inherently dielectric as determined by their complex morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Second, a sharp rise in the conductivity curves at higher frequency region is attributed to the fast movement of charge carriers with the application of high electric field. It is because when we are applying a high electric field to the polymer‐ceramic composites maximum numbers of charges are migrated to the ceramic interface …”
Section: Dielectric and Electrical Propertiesmentioning
confidence: 99%
“…Second, a sharp rise in the conductivity curves at higher frequency region is attributed to the fast movement of charge carriers with the application of high electric field. It is because when we are applying a high electric field to the polymer‐ceramic composites maximum numbers of charges are migrated to the ceramic interface …”
Section: Dielectric and Electrical Propertiesmentioning
confidence: 99%
“…Using in-situ tensile testing, Raihan et al [11] induced damage in an off-axis plain weave E-glass fabric combined with epoxy resin matrix and performed dielectric studies on the samples to get real time response with damage as shown in Figure 3(a). Also, a novel edge replication technique was used to observe the damage progression with increasing load as shown in Figure 3 In this paper we induce damage in the specimen and capture the change in material state using the concept of "Heterogeneous" fracture mechanics and predict the "beginning" of end of life.…”
Section: Experimental Results and Motivationmentioning
confidence: 99%
“…Haider [10], Raihan et al [11] [12] [13], Bekas et al [14] have demonstrated the capability of this technique to characterize and detect damage in composite material systems. Most recently, Reifsnider et al [15] have postulated the concept of a "critical" path generated by coalescence of various defects and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of previous publications, we have applied equation (3) to some of the complex microstructures illustrated in Figure 1 at the conformal level, and have included electrochemical effects on the resulting flux terms shown in that equation. However, in this publication, we are only concerned with constructing a predictive method for time dependent electric charge distribution (including surface charge) in heterogeneous materials at the fundamental level, and the validation of such a method (Liu 2012;Liu 2011a;Reifsnider et al 2013;Baker et al 2014;Liu 2011b;Raihan et al 2014). Therefore, without loss of generality for the present discussion, we neglect all source terms and concern ourselves with the following simplified version of Eq.…”
Section: Methodsmentioning
confidence: 99%